Demographic variation in continuous glucose monitoring utilisation among patients with type 1 diabetes from a US regional academic medical centre: a retrospective cohort study, 2018–2021 - Min-Woong Sohn; Mary E Lacy; Omer Atac; Kory R Heier; Daniela Moga; John Fowlkes; Aaron J Kruse-Diehr; Teresa M Waters (BMJ Open)
Objective While continuous glucose monitoring (CGM) utilisation has been increasing among patients with type 1 diabetes (T1D), few studies have examined patterns of use across age, race/ethnicity and insurance status together. In this study, we examine CGM utilisation among patients with T1D from a regional academic medical centre across all insurance types.Design and setting This is a retrospective cohort study including both paediatric and adult patients with T1D who visited a regional academic medical centre between 1 January 2018 and 31 December 2021.Methods Patients were followed from the date of their first T1D encounter during the study period until the first of the following: CGM use was documented, ≥730 days with no encounters at this centre or the end of the study period. We compared CGM use across demographic and clinical characteristics and used logistic regression models to assess the association between demographic variables and CGM utilisation.Results Among 3311 eligible patients with T1D, CGM utilisation was 51.22%. The highest utilisation rates were among patients <18 years old while the lowest rates were among those in the 65+ years age group. Patients with private insurance and those who attended diabetes self-management education and support (DSMES) programmes had significantly higher CGM utilisation than those with public insurance and those who did not attend DSMES, respectively. In models stratified by age, we examined patterns of CGM use across insurance categories and found that CGM rates were persistently low among those with public versus private insurance.Conclusions In this retrospective review of patients with T1D receiving care at a regional academic medical centre from 2018 to 2021, nearly half of our sample used CGM. However, we found substantial variation in CGM utilisation with lower rates among older versus younger adults and individuals covered by public versus private insurance. Enhancing CGM access is important to mitigate diabetes-related complications for all patients with T1D.